Keeping up with the e-Joneses: Do Online Social Networks Raise Social Comparisons? - Fabio Sabatini; Francesco Sarracino (Fondazione Eni Enrico Mattei (FEEM), 2016)
Online social networks, such as Facebook, disclose an unprecedented volume of personal information amplifying the occasions for social comparisons, which can be a cause of frustration. We test the hypothesis that the use of social networking sites (SNS) increases social comparisons as proxied by people's dissatisfaction with their income and we compare the effect of SNS in Western and Eastern European countries. After controlling for the possibility of reverse causality, our results suggest that SNS users have a higher probability to compare their achievements with those of others. In Western countries, this leads individuals to a lower satisfaction with their economic conditions. The opposite holds in Eastern countries, where upward comparisons seemingly strengthen the hope that an improvement in individuals' economic conditions will occur (so called “tunnel effect”). We conclude that SNS can be a strong engine of frustration for their users depending on the institutional and economic circumstancesKeywords: Social Networks, Social Networking Sites, Social Comparisons, Satisfaction with Income, Relative Deprivation
Keywords: D83; I31; O33; Z1; Z13; 330